Perioperative mortality among geriatric patients in Ethiopia: a prospective cohort study - Endeshaw, Amanuel Sisay; Molla, Misganew Terefe; Kumie, Fantahun Tarekegn (Frontiers in Medicine, 2023)
Background: With the dramatic growth in the aged population observed in developed and developing nations, the older population burdened by unmet demand for surgical treatment has become a significant yet unnoticed public health concern in resource-limited countries. Studies are limited regarding surgical mortality of geriatric patients in Africa. Therefore, this study aims to estimate the incidence and identify predictors of postoperative mortality using prospective data in a low-income country, Ethiopia.A prospective cohort study was conducted from June 01, 2019, to June 30, 2021, at a tertiary-level hospital in Ethiopia. Perioperative data were collected using an electronic data collection tool. Cox regression analysis was used to identify predictor variables.The association between predictors and postoperative mortality among geriatrics was computed using a hazard ratio (HR) with a 95% confidence interval (CI); p-value <0.05 was a cutoff value to declare statistical significance.Results: Of eligible 618 patients, 601 were included in the final analysis. The overall incidence of postoperative mortality among geriatrics was 5.15%, with a rate of 1.91 (95% CI: 1.34, 2.72) deaths per 1000 person-day observation. Age ≥80 years (Adjusted hazard ratio (AHR)=2.59, 95%